Six-month outcomes after individualized nutritional support during the hospital stay in medical patients at nutritional risk: Secondary analysis of a prospective randomized trial. Issue 3 (March 2021) - Kaegi-Braun, Nina; Tribolet, Pascal; Gomes, Filomena; Fehr, Rebecca; Baechli, Valerie; Geiser, Martina; Deiss, Manuela; Kutz, Alexander; Bregenzer, Thomas; Hoess, Claus; Pavlicek, Vojtech; Schmid, Sarah; et al.
Summary: Background: Among medical inpatients at risk of malnutrition, the use of individualized nutritional support during the hospital stay was found to reduce complications and improve mortality at short-term. We evaluated clinical outcomes at 6-months follow-up. Methods: We randomly assigned 2028 patients to receive protocol-guided individualized nutritional support to reach protein and energy goals (intervention group) or hospital food as usual (control group) during the hospital stay. The intervention was discontinued at hospital discharge and further nutritional support was based on the discretion of the treating team. We had complete follow-up information of 1995 patients (98%), which were included in the final analysis. The primary endpoint was all-cause mortality at 6-months. Prespecified secondary end points included non-elective hospital readmissions, functional outcome and quality of life. Results: At 6-month, 231 of 994 (23.2%) intervention group patients had died compared to 246 of 999 (24.6%) control group patients, resulting in a hazard ratio for death of 0.90 (95%CI 0.76 to 1.08, p = 0.277). Compared to control patients, intervention group patients had similar rates of hospital readmission (27.3% vs. 27.6%, HR 1.00 (95%CI 0.84 to 1.18), p = 0.974), falls (11.2% vs. 10.9%, HR 0.96 (95%CI 0.72 to 1.27), p = 0.773) and similar quality of life and activities of daily living scores. Interpretation: While individualized nutritional support during the hospital stay significantly reduced short-term mortality, there was no legacy effect on longer term outcomes. Future trials should investigate whether continuation of nutritional support after hospital discharge reduces the high malnutrition-associated mortality rates in this vulnerable patient population. Trial registration: ClinicalTrials.gov number, NCT02517476.